Lone survivor - Berg, Peter, 1964-; Wahlberg, Mark, 1971-; Kitsch, Taylor, 1981-; Hirsch, Emile, 1985- (Universal City, CA : Universal Studios Home Entertainment, 2014)
Four Navy SEALs enter Afghanistan to neutralize a high-level al-Qaeda member and find themselves in an enemy ambush alone, fighting for their lives.
Originally released as a motion picture in 2013.
Based on the book by Marcus Luttrell and Patrick Robinson.
Dolby digital 5.1, wide screen 2.40:1.
Features: Bringing the story to light, The fallen heroes of Operation Red Wings.
Mark Wahlberg, Taylor Kitsch, Emile Hirsch, Ben Foster, Eric Bana.
MPAA rating: R.
Keywords: Luttrell, Marcus -- Drama; Luttrell, Marcus -- Film adaptations; Robinson, Patrick, -- 1939- -- Film adaptations; Operation Red Wings, 2005 -- Drama; War on Terrorism, 2001-2009 -- Drama; Afghan War, 2001-2021 -- Drama; Action and adventure films; Fiction films; Video recordings for the hearing impaired; Based on the book; Feature films; Biographical films; War films; Historical films